Duality of (h,φ)-Multiobjective Programming Involving Generalized Invex Functions - GuoLin Yu (Journal of Applied Mathematics)
In the setting of Ben-Tal's generalized algebraic operations, this paper deals with Mond-Weir type dual theorems of multiobjective programming problems involving generalized invex functions. Two classes of functions, namely, (h,φ)-pseudoinvex and (h,φ)-quasi-invex, are defined for a vector function. By utilizing these two classes of functions, some dual theorems are established for conditionally proper efficient solution in (h,φ)-multiobjective programming problems.